2018
DOI: 10.1186/s40779-018-0162-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spaceflight and simulated microgravity on microbial growth and secondary metabolism

Abstract: Spaceflight and ground-based microgravity analog experiments have suggested that microgravity can affect microbial growth and metabolism. Although the effects of microgravity and its analogs on microorganisms have been studied for more than 50 years, plausible conflicting and diverse results have frequently been reported in different experiments, especially regarding microbial growth and secondary metabolism. Until now, only the responses of a few typical microbes to microgravity have been investigated; system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 97 publications
1
99
0
Order By: Relevance
“…Our findings show that clinostat rotation results in higher levels of organic acid accumulation and lower levels of metabolite transport from cells to the medium. This finding, together with that reported by Huang and colleagues (28), suggests that clinostat rotation has a significant impact on the metabolism of microorganisms. Moreover, the pathway analysis revealed that clinostat rotation mainly affected amino acid metabolism and the energy-related metabolic pathways of A. carbonarius.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Our findings show that clinostat rotation results in higher levels of organic acid accumulation and lower levels of metabolite transport from cells to the medium. This finding, together with that reported by Huang and colleagues (28), suggests that clinostat rotation has a significant impact on the metabolism of microorganisms. Moreover, the pathway analysis revealed that clinostat rotation mainly affected amino acid metabolism and the energy-related metabolic pathways of A. carbonarius.…”
Section: Discussionsupporting
confidence: 77%
“…This finding illustrates that clinostat rotation affects the transport of these metabolites from the cell into the medium and is consistent with results reported by Brown (39), who found that clinostat rotation alters transport phenomena in the cell's external fluid environment. It is also widely accepted that the adaptive response of cells to the changing microenvironment, including the extracellular nutrient distribution and the transport of metabolites by fluid dynamics, is an important pathway for the response of microorganisms to microgravity (28). Huang et al (28) reported that the extracellular microenvironment affects the secretion and transport of secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microgravity conditions provide conflicting results on microbial growth and virulence of opportunistic human pathogens (Morrison et al, 2017;, while the analysis of archival samples generates a detrimental time gap for a flight-supportive result interpretation (Huang et al, 2018;Novikova et al, 2006). HPC was proved to be also affected by carbon sources in cultivation media, the incubation time, and the initial microbial load level (Amalfitano et al, 2018b).…”
mentioning
confidence: 99%